225k views
3 votes
What is the answer to
–5(x + 7) = 3x + 29

2 Answers

1 vote
x= -8
Step 1. You have to distribute -5 through the parentheses and you will get -5x-35=3x+ 29
Step 2. Move variable to the left-hand side and change its sign and get -5x-3x- 35= 29 Part 2. Move constant to the right-hand side and change its sign -5x-3x=29+35
Step 3. Collect the like terms -8x=29+35
Part 2. Add the numbers -8x=64
Step 4. Divide both side of the equation by -8
User Brondahl
by
5.9k points
4 votes

Answer:

x = -8

Explanation:

User Mike Schenk
by
6.1k points